KONSEP HIDUP BAHAGIA DI DUNIA DAN AKHIRAT - Samani Samani; Imam Mashudi Latif (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2024)
This article focuses on a happy life according to the Qur'an. Happiness is described using the term sa'ada. Explaining several concepts of happiness that are also quoted from several scholars and scientists, as well as Muslim and non-Muslim practitioners as a comparison. This research is a type of library research, book survey or documentary research. The process of collecting data from various literatures, both in libraries and other places, such as other written document materials, such as magazines, newspapers and others. Data analysis uses Content Analysis which is directed at exploring documents or texts that are widely published regarding the theme of the research. The results of the study indicate that there is a common misunderstanding that happiness is described as material excess, abundant wealth, luxury, reward and heaven. The concept of happiness according to Islam can be obtained in the world and also in the hereafter. The Qur'an distinguishes between pleasure and happiness. Happiness (al-sa'a>dah, al-falah) is not only about fulfilling desires or lusts, but also two important aspects in ourselves, namely affective (emotional) and cognitive (logical). This is also different from pleasure (pleasure, al-farh, al-surru>r).